2003
DOI: 10.1038/sj.cdd.4401324
|View full text |Cite
|
Sign up to set email alerts
|

Life and death decisions by E2F-1

Abstract: Deregulation of the transcription factor E2F-1 is a common event in most human cancers. Paradoxically, E2F-1 has been shown to have the ability to induce both cell cycle progression and programmed cell death, leading potentially to both tumour-promoting as well as tumour-suppressive effects. Although the pathway to cell cycle progression seems straightforward with a number of growth-promoting E2F target genes having been described, the pathways to apoptosis are less well defined and more complex. The discovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
135
1
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(140 citation statements)
references
References 86 publications
1
135
1
3
Order By: Relevance
“…E2F1 is a transcription factor involved in cell-cycle control and apoptosis, whose expression is often dysregulated in human tumors. 32,33 Upon DNA damage, E2F1 is phosphorylated by CHK1 and CHK2 and subsequently induces transcription of p73 and its target genes to initiate p53-independent apoptosis. 34 Studies on murine embryonic fibroblasts indicated that the AHR inhibits E2F1-induced apoptosis, probably due to a physical interaction of both transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…E2F1 is a transcription factor involved in cell-cycle control and apoptosis, whose expression is often dysregulated in human tumors. 32,33 Upon DNA damage, E2F1 is phosphorylated by CHK1 and CHK2 and subsequently induces transcription of p73 and its target genes to initiate p53-independent apoptosis. 34 Studies on murine embryonic fibroblasts indicated that the AHR inhibits E2F1-induced apoptosis, probably due to a physical interaction of both transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptional activator E2F1 has been shown to upregulate the expression of many genes involved in differentiation, proliferation and apoptosis, and it plays a major role in the G1/S transition and DNA synthesis (Bell and Ryan, 2004). Prohibitin represses the transcriptional activity of E2Fs1-5 by recruiting co-repressors, including histone deacetylase 1, N-CoR and BrG1/ Brm (Wang et al, 2002), whereas Rb represses the transcriptional activity of E2Fs1-3 by recruiting histone deacetylase 1, DNA methyltransferase and BrG1/Brm (Luo et al, 1998;Magnaghi-Jaulin et al, 1998;Zhu, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The E2F family of transcription factors is a group of DNA-binding proteins that are involved in cell-cycle progression, and therefore play a key role in cell proliferation (4). E2F1has a more pivotal role than other E2Fs, due to its unique character of inducing both cell-cycle progression and apoptosis (5).…”
Section: Introductionmentioning
confidence: 99%